Bridge over troubled waters linking climate change and development - Agrawala, Shardul (2005)
This book is the product of a collaborative effort between the OECD Environment and Development Cooperation directorates on mainstreaming responses to climate change in development planning and assistance. This volume synthesizes insights from six country case studies that review climate change impacts and vulnerabilities, analyze relevant national plans and aid investments in terms of their exposure and attention to climate risks, and examine in-depth key systems where climate change is closely intertwined with development and natural resource management. The case studies cover the Nepal Himalayas, Mount Kilimanjaro in Tanzania, the Nile in Egypt, the Bangladesh Sundarbans, coastal mangroves in Fiji, and agriculture and forestry sectors in Uruguay.--Publisher's description.
Keywords: Klimaveränderung / Entwicklungsplanung / Entwicklungshilfe / Entwicklungsländer; Klimaänderung; Umwelt; Wirtschaftsentwicklung; Cambios climáticos -- Aspectos económicos; Climate and civilization; Climatic changes -- Economic aspects; Desarrollo económico -- Aspectos ambientales; Desarrollo económico -- Factores climáticos; Economic development -- Environmental aspects; Economische ontwikkeling.; Klimaatveranderingen.; Umweltpolitik; Entwicklungspolitik; Entwicklungsländer